Heterogeneous beliefs and housing-market boom-bust cycles in a small open economy - Hajime Tomura (Bank of Canada, 2009)
This paper introduces heterogeneous beliefs among households in a small open economy model for the Canadian economy. The model suggests that simultaneous boom-bust cycles in house prices, output, investment, consumption and hours worked emerge when credit-constrained mortgage borrowers expect that future house prices will rise and this expectation is neither shared by savers nor realized ex-post. With sticky prices and a standard monetary policy rule, the model shows that the nominal policy interest rate and the CPI inflation rate decline during housing booms and rise as house prices fall. These results replicate the stylized features of housing-market boom-bust cycles in industrialized countries. Policy experiments demonstrate that stronger policy responses to inflation amplify housing-market boom-bust cycles. Also, higher loan-to-value ratios amplify housing-market boom-bust cycles by encouraging speculative housing investments by mortgage borrowers during housing booms and increasing liquidation of housing collateral during housing busts.
Keywords: E44; E52; 330; Credit and credit aggregates; Financial stability; Inflation targets; Immobilienpreis; Verschuldungsrestriktion; Entscheidung bei Unsicherheit; Preisrigidität; Zins; Geldpolitik; Inflation Targeting; Kanada